2021
DOI: 10.3389/fpsyg.2021.661278
|View full text |Cite
|
Sign up to set email alerts
|

Character Strengths Predict Subjective Well-Being, Psychological Well-Being, and Psychopathological Symptoms, Over and Above Functional Social Support

Abstract: The increasing value of character strengths in the prediction of well-being and psychopathology, after the effects of functional social support and sociodemographic variables are accounted for, is examined. Participants were 1494 Spanish-speaking students between the ages of 18 and 68 (43.3% men and 56.7% women) who completed measures of character strengths, functional social support, subjective well-being, psychological well-being, and symptoms of psychopathology. Functional social support had predictive valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 70 publications
0
6
0
1
Order By: Relevance
“…This classification was developed by social scientists who identified 24 strengths and organized them under six overarching categories: Wisdom, Courage, Humanity, Justice, Temperance, and Transcendence (Peterson & Seligman, 2004). We selected the VIA classification because it has been central in positive psychology, is broad and comprehensive, and the strengths have been consistently related to better happiness and well-being (Azañedo et al, 2021;Wagner et al, 2019) and interventions have been shown to increase them (Green, 2021;Niemiec, 2017). We thought that focusing on strengths would be more likely to result in lasting changes in key personal characteristics that might sustain and continue to improve happiness, health, and wellbeing (Luthans & Youssef-Morgan, 2017).…”
Section: The Current Studymentioning
confidence: 99%
“…This classification was developed by social scientists who identified 24 strengths and organized them under six overarching categories: Wisdom, Courage, Humanity, Justice, Temperance, and Transcendence (Peterson & Seligman, 2004). We selected the VIA classification because it has been central in positive psychology, is broad and comprehensive, and the strengths have been consistently related to better happiness and well-being (Azañedo et al, 2021;Wagner et al, 2019) and interventions have been shown to increase them (Green, 2021;Niemiec, 2017). We thought that focusing on strengths would be more likely to result in lasting changes in key personal characteristics that might sustain and continue to improve happiness, health, and wellbeing (Luthans & Youssef-Morgan, 2017).…”
Section: The Current Studymentioning
confidence: 99%
“…The researchers suggest that this is a preliminary indication of the influence of the existing Chinese culture on the overall view of death in the nursing population: the Chinese people's "respectful and distant" avoidance of death has led young and unmarried people who are enjoying the present moment to dilute their thoughts about death with the good life in front of them, while as people grow older and continue to live with marriage, they have to face the inevitable death. Nurses who have experienced marriage, due to their age, experience and family, realize the importance of spirituality and are fully aware of the positive impact of spirituality, and are more likely to think more deeply about death, empathize with patients and understand their spiritual needs, so they can give more targeted spiritual care according to their spiritual needs (Azañedo et al, 2021). Note: R = 0.762, R 2 = 0.580, adjusted R 2 = 0.567, F = 43.357, p < 0.001.…”
Section: Marital Statusmentioning
confidence: 99%
“…The psychological capital of married nurses was higher than unmarried nurses. Functional social support could protect individuals from psychological problems by buffering the negative effect of life stressors on mental health and promoting wellbeing (Azanedo et al, 2021). The spiritual orientation of nurses has a positive effect on psychological capital.…”
Section: Marital Statusmentioning
confidence: 99%